More stories from Langley : another glimpse inside the CIA - Mickolus, Edward F. (Lincoln : Potomac Books, An imprint of the University of Nebraska Press, 2020)
"Collection of personal essays detailing the adventures, advice, and experience of generations of CIA support and technical officers"--
Do your brother a favor : apply to CIA / Elizabeth Arens -- Reflections from an analytical change agent : twenty-seven years and counting / acurrently serving DI officer -- What's a librarian do at the CIA? / Peggy Tuten -- More of what a librarian does at the CIA / Kim Condas -- Getting to do what I was meant to do / Robert Kresge -- We're not in Kansas-er, Missouri-anymore! / Mary O'Sullivan -- My thirty years in scientific and weapons intelligence at CIA / Julian Nall -- The pathway of a life unnoticed / Michael Douglas Smith -- The DIToolkit : don't leave home without it / Janet Stiegler -- A nightmare come true / Elinor Houghton Kelly -- How Hoosier basketball and spying came together in Moscow during the Cold War / GeneArthur Coyle -- How intelligence saved the Pope / Terrence L. Williams -- Flirting with the Directorate of Intelligence : a Directorate of Operations officer's short story / Bob Phillipson -- Soldier, sailor, artist, spy / Chip Beck -- Terminating an asset / Doug Patteson -- The rocky but interesting road of intelligence-policy relations / Paul R. Pillar -- Cement, speeches, terrorism, and stray cats / Susan Hasler -- Rock star or CIA officer / Kathy Thomas -- An accidental career of consequence / Jeff J. Johnson -- Developing a better understanding of the personal dimensions of working at the CIA / Hector J. Escobar, III -- Beginnings / Lester Paldy -- My career as a CIA logistics professional, 1986-2013 / James R. Pasqualini -- Black programs and services / Robert M. Blansfield -- The CIA Book of Honor / Doug Patteson -- Camp Chapman / Doug Patteson -- Prince and the revolution : the re-engineering of open source intelligence collection / Doug Naquin -- Bell ringers! / Elinor Houghton Kelly -- Ode to new CIA members / Ed Mickolus.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Biography -- Anecdotes. 610.; United States. -- Central Intelligence Agency -- History -- Anecdotes; United States. -- Central Intelligence Agency; Intelligence officers -- United States -- Biography -- Anecdotes; Spies -- United States -- Biography -- Anecdotes; Intelligence service -- United States -- Anecdotes; Officiers de renseignements -- États-Unis -- Biographies -- Anecdotes; Employees; Intelligence officers; Intelligence service; Spies; United States; Anecdotes; Biographies; History